2016
DOI: 10.1242/jeb.132183
|View full text |Cite
|
Sign up to set email alerts
|

Current versus future reproduction and longevity: a re-evaluation of predictions and mechanisms

Abstract: Oxidative damage is predicted to be a mediator of trade-offs between current reproduction and future reproduction or survival, but most studies fail to support such predictions. We suggest that two factors underlie the equivocal nature of these findings: (1) investigators typically assume a negative linear relationship between current reproduction and future reproduction or survival, even though this is not consistently shown by empirical studies; and (2) studies often fail to target mechanisms that could link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 185 publications
(228 reference statements)
1
57
0
Order By: Relevance
“…Furthermore, telomeres have been shown to shorten in response to both increased reproductive effort (Reichert et al, 2014) and stressful environmental conditions (Stier et al, 2014b(Stier et al, , 2015bMeillere et al, 2015;Simide et al, 2016). Additionally, recent work suggests that changes in mitochondrial bioenergetics and ROS production during reproduction are potential key mechanisms underlying the costs of reproduction (Zhang and Hood, 2016). Non-mammalian vertebrates like the aspic viper will offer great opportunities in the future to study such questions in a minimally invasive manner as their RBCs possess functional mitochondria, unlike those of mammalian species (Stier et al, 2013(Stier et al, , 2015a(Stier et al, , 2017.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, telomeres have been shown to shorten in response to both increased reproductive effort (Reichert et al, 2014) and stressful environmental conditions (Stier et al, 2014b(Stier et al, , 2015bMeillere et al, 2015;Simide et al, 2016). Additionally, recent work suggests that changes in mitochondrial bioenergetics and ROS production during reproduction are potential key mechanisms underlying the costs of reproduction (Zhang and Hood, 2016). Non-mammalian vertebrates like the aspic viper will offer great opportunities in the future to study such questions in a minimally invasive manner as their RBCs possess functional mitochondria, unlike those of mammalian species (Stier et al, 2013(Stier et al, , 2015a(Stier et al, , 2017.…”
Section: Resultsmentioning
confidence: 99%
“…However, the proximate physiological determinants of this cost remain under debate (Metcalfe and Monaghan, 2013;Zhang and Hood, 2016). Several studies have suggested oxidative stress as one potential physiological mediator of this life history trade-off (Monaghan et al, 2009;Stier et al, 2012;Metcalfe and Monaghan, 2013;Speakman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reproduction in mammals is a period of high reproductive plasticity (Hood et al. ), with physiological changes that can alter a female's physiology for the remainder of her lifespan (Zhang and Hood ). We found that the primiparous and multiparous females showed no differences with respect to oxygen consumption and glycolytic rates compared with virgin females and had significantly lower rates of oxidative damage which was likely facilitated by the utilization of their endogenous antioxidant reserves.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we would expect that having offspring may negatively affect the metabolic and oxidative stress profiles of the mother, in terms of increased energy expenditure and potential increases in oxidative damage. However, pregnancy does not seem to negatively affect mitochondrial ATP production, and may even increase the number of antioxidants produced by the individual (Schmidt and Hood ; Zhang and Hood ). This indicates that a single pregnancy itself may not be inherently detrimental to mothers, and may even provide some physiologically protective effects.…”
Section: Introductionmentioning
confidence: 99%
“…Cells and organs may compensate for a drop in RCR by increasing the number of mitochondria present through mitochondrial biogenesis (Pichaud, Garratt, Ballard, & Brooks, 2013). In contrast, the P/O ratio targets the coupling efficiency of the mitochondria and substrate oxidation (Salin, Auer, Rey, Selman, & Metcalfe, 2015;Zhang & Hood, 2016). Change in P/O reflects changes in the proton motive force across the inner mitochondrial membrane due to a change in the activity of uncoupling proteins, adenine nucleotide transporters, and the fatty acid content of the lipid bilayer.…”
Section: Introductionmentioning
confidence: 99%